2023
DOI: 10.3389/fnut.2023.1187165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a wholegrain-rich diet on markers of colonic fermentation and bowel function and their associations with the gut microbiome: a randomised controlled cross-over trial

Abstract: BackgroundDiets rich in whole grains are associated with health benefits. Yet, it remains unclear whether the benefits are mediated by changes in gut function and fermentation.ObjectiveWe explored the effects of whole-grain vs. refined-grain diets on markers of colonic fermentation and bowel function, as well as their associations with the gut microbiome.MethodsFifty overweight individuals with increased metabolic risk and a high habitual intake of whole grains (~69 g/day) completed a randomised cross-over tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The release of multiple MCFAs might indicate the concerted action of different microbial groups cooperating in a food breakdown web 38 40 . A similar mechanism where MCFAs were released during the anaerobic breakdown of complex organic matrixes by anaerobic cultures was elucidated using time-resolved metatransciptomics by Scarborough et al 38 .Furthermore, the release of MCFAs, as an oat bran signature, has been described in few intestinal fermentation experiments in-vitro and recently reported during an in-vivo intervention 36 , 41 . In general, the possibility to easily monitor and understand the change in VOCs depending on the dietary substrate and donor under study can reveal less-obvious dynamics occurring when studying microbe-diet interactions in-vitro.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The release of multiple MCFAs might indicate the concerted action of different microbial groups cooperating in a food breakdown web 38 40 . A similar mechanism where MCFAs were released during the anaerobic breakdown of complex organic matrixes by anaerobic cultures was elucidated using time-resolved metatransciptomics by Scarborough et al 38 .Furthermore, the release of MCFAs, as an oat bran signature, has been described in few intestinal fermentation experiments in-vitro and recently reported during an in-vivo intervention 36 , 41 . In general, the possibility to easily monitor and understand the change in VOCs depending on the dietary substrate and donor under study can reveal less-obvious dynamics occurring when studying microbe-diet interactions in-vitro.…”
Section: Discussionmentioning
confidence: 83%
“…The clustering analysis, which organized VOCs into sub-clusters based on similar time-dependent profiles, highlighted the complexity and substrate-specific nature of these microbial transformations starting from the same microbial inoculum. Furtermore, the clustering of VOCs molecular profiles provides useful information about the system’s molecular behaviour 36 . Grouping molecules with the same time pattern is an indication to understand which molecules can be co-regulated or participate in the same biological processes 37 .…”
Section: Discussionmentioning
confidence: 99%
“…However, dietary fibres are heterogenous compounds, and different fibre types can evoke different biologic responses [ 68 , 102 ]. A wholegrain fibre diet increased the level of butyrate in overweight individuals [ 103 ]. Accordingly, a recent study found that a dietary fibre’s effect depended on the fibre type, the patient immune status and the fermentative capacity of their gut microbiota [ 21 ].…”
Section: Interactions Between Diet Gut Microbiota and Host Factorsmentioning
confidence: 99%